Signal transduction: hanging on a scaffold. - Burack, W.R.; Shaw, A.S. (Current Opinion in Cell Biology, 2000)
Recent data concerning scaffolding proteins profoundly challenge our conceptions of multicomponent signal transduction systems. Recent studies of the phototransduction system in Drosophila suggest two points. First, scaffolding markedly limits the possibilities for signal amplification. Second, the methods generally available to study signal transduction may be too crude to assess the in vivo roles of scaffolds. Studies of the mitogen-activated protein kinase pathway scaffold, Ste5, indicate functions beyond that of a passive structural element. Finally, the identification of new mitogen-activated protein kinase pathway scaffolds suggests the existence of multiple 'signalosomes' or 'transducisomes'.